Hubungan Asupan Cairan Dengan Penambahan Berat Badan Interdialisis Pada Pasien Hemodialisis Di RSUD Kota Tanjungpinang - Yusnaini Siagina; Harisman Trialvi (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2020)
Chronic kidney disease (CKD) is a failure to maintain metabolic function and fluid and electrolyte balance due to the progressive destruction of renal structures degan buildup of residual metabolic manifestations (toxic uremic) in the blood. Hemodialysis is a method of dialysis used to remove fluid and waste products from the body when it is acute or progressive renal unable to perform the process by using a machine equipped with a semi-permeable membrane filter (artificial kidney). The purpose of this study was to determine the relationship of fluid intake with weight gain interdialytic undergoing hemodialysis in hospitals Tanjungpinang. This study uses a quantitative method with anatik survey and design cross-sectional The sample size of 16 people, with a sampling technique purposive were analyzed by test. Pearson correlation results of the analysis showed the r -0,907 and p-value 0.000 p <αof 0.1, which means there is a connection with the fluid intake, weight gain interdialytic In hemodialysis in hospitals Tanjungpinang. the results of this study are expected for hemodialysis nurses in order to improve the quality in the development of nursing science can provide fluid management education to patients experiencing excessive weight gain (5% of the dry BB).Keywords: Fluid Intake, Hemodialysis, Weight Gain Interdialisis